RISK MANAGEMENT IN OIL AND GAS SECTOR - Halliday, Joyce Nnenna (2005)
The objective of this dissertation is to examine risk management in the oil and gas sector with particular reference to the use of captives as a tool for risk transfer. The oil and gas sector has the biggest companies in the world and operate internationally. As a result of changes in the geopolitical and economic climate the sector is faced with new challenges such as consolidation, increased business interruption exposures, growing regulatory pressures, continued global competition etc. These further expose the business of oil and gas exploration and production to uncertainties arising from their operations, the market, the environment, and political issues. Standard risk management procedures are adopted to manage these risks holistically. These procedures consist of continual processes of risk identification, risk estimation, risk evaluation, risk treatment, and risk monitoring and control. In the course of risk treatment certain strategic decisions are taken depending on the evaluated impact of the project outcome on the organisation. Some of these decisions are avoidance, control, cooperation, imitation and flexibility (Miller, 1991). The oil and gas sector opts for controlling insurable risk through the use of captives as a transfer tool. The captives commonly used are single parent captives (owned by the individual companies). The group captives are not common but there are the association captives. This research finds out that the sector claims that the use of captives, which is seen as self-insurance is adopted due to the fact that the conventional insurance companies are risk averse and would not provide them with the capacity of cover needed for their high-risk operations. But the conventional insurers refute this arguing that the sector sees itself as too big to allow risk sharing so would rather retain its risk for the benefit of cash flow management. The research further examines a case study on a disaster in an organisation in the sector, and finds out that typically industrial accidents are caused by management errors.